Analysis of social forestry governance in Jeneberang I forest manajement unit. Issue 1 (April 2020) - Solie, A T; Supratman,; Malamassam, D; Ridwan,
Abstract: Social forestry is one of the Ministry of Forestry policies in alleviating poverty and creating employment for people in and around forests, and forests sustainability. Social forestry governance is one of the important things in evaluating the performance of social forestry policy implementation. This study aims to analyze 5 key elements of social forestry governance, referring to Cadman T. (2011), that is interest representation, accountability and transparency, decision-making, and implementation. The study was conducted in the KPH Jenneberang I area, Gowa Regency, South Sulawesi Province. Two groups of social forestry scheme permit holders were selected purposively as research locations. Primary and secondary data were obtained through field observations, in-depth interviews, Focus Group Discussions (FGD), and documentation studies. The study found that the implementation of social forestry policy with the target area as the main indicator of performance achievements has implications for the suboptimal quality of social forestry governance. Conflicts between the community and the government and between the community and the community are the effects of current governance. Changing the target area of social forestry licenses to target the number of social forestry business groups operating as key indicators of performance achievements, becoming one of the solutions to optimize the quality of social forestry governance.